Experimental and numerical studies of the eccentric compressive behavior of circular RC columns strengthened with grouting-filled steel tubes - Xiao Hu; Zhenlin Chen (Ain Shams Engineering Journal, 2023)
The reinforcement of concrete columns with steel tubes is a convenient and economical technique in civil engineering. To investigate the mechanical behavior of short circular concrete columns strengthened with grouting-filled steel tubes under eccentric compressive loads, five specimens with different eccentricities were tested in the present work. Finite element simulations were carried out in ABAQUS software to analyze the mechanical behavior of the reinforced columns. A parametric study was performed to evaluate the influences on the SRF, RCR, P-M, and P/Pu-M/Mu curves of the reinforced columns. The results showed that increasing the yield strength and thickness of the steel tube improved the performance of the reinforced columns. The ultimate load-carrying capacities of the specimens determined by the codes were compared with those determined by the proposed formulas. The results also showed that the ultimate load-carrying capacities of the specimens determined by the proposed formulas were more accurate.